(untitled) (Baghdad Science Journal, 2005)
Proved the validity of all mixtures or not to accept the bees and then resistant infection worm wax Minor has accepted honey bee colonies all mixtures beeswax with paraffin wax industrial all ratios used made ??of a mixture to DVD waxy full and used naturally in breeding Houdnth In store honey and pollen evendiversified Bravian and natural wax